Transcription of Interleukin-25 and Extracellular Release of the Protein Is Regulated by Allergen Proteases in Airway Epithelial Cells - Kouzaki, Hideaki (Am J Respir Cell Mol Biol, 2013)
Epithelial cells at mucosal surfaces are integral components of innate and adaptive immunity. IL-25 is reportedly produced by epithelial cells and likely plays vital roles in regulating type-2 immune responses. However, little is known regarding the mechanisms that control production and extracellular releases of IL-25. We hypothesized that proteases from the multiple allergens may induce IL-25 production in airway epithelial cells. In this study, we found that IL-25 is constitutively produced and detectable in cytoplasm of resting normal human bronchial epithelial (NHBE) cells. When exposed to airborne allergens such as house dust mite (HDM), stored IL-25 was released rapidly to the extracellular space. IL-25 release was not accompanied by cell death, suggesting involvement of active secretory mechanism(s). HDM also enhanced IL-25 mRNA transcription, which was dependent on their protease activities. Furthermore, activation of NHBE cells with authentic proteases, such as trypsin and papain, or with a peptide agonist for protease-activated receptor 2 was sufficient to enhance IL-25 mRNA transcription and protein. Protease-driven increase in mRNA transcription and allergen-driven extracellular release of IL-25 protein was also observed in primary nasal epithelial cells from healthy individuals. These findings suggest that IL-25 production by airway epithelial cells is regulated by the transcription and protein release levels and that allergen proteases likely play pivotal roles in both biological processes.